Entrepreneurship - Keister, Lisa A., 1968- (Research in the sociology of work, 2005)
Entrepreneurship, the creation of new economic entities, is central to the structure and functioning of organizations and economies. New business formation also shapes the nature of social and economic stratification in an economy and may be an important vehicle for social mobility. The papers in this volume explore many of the issues that are central to the study of entrepreneurship today and also break new ground in the field. The papers explore the importance of entrepreneurship, the process by which entrepreneurship occurs, and the way both meaning and process vary with context and opportunity structures.These papers address long-standing controversies in the study of entrepreneurship, and they also identify new, innovative questions and approaches. As a result, both seasoned entrepreneurship researchers and those who are new to the field will find the papers interesting and useful. Research in the Sociology of Work is now available online at ScienceDirect full-text online of volumes 10 onwards.